2022
DOI: 10.1186/s12915-022-01388-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly and population genomic analyses provide insights into adaptive evolution of the red turpentine beetle, Dendroctonus valens

Abstract: Background Biological invasions are responsible for substantial environmental and economic losses. The red turpentine beetle (RTB), Dendroctonus valens LeConte, is an important invasive bark beetle from North America that has caused substantial tree mortality in China. The lack of a high-quality reference genome seriously limits deciphering the extent to which genetic adaptions resulted in a secondary pest becoming so destructive in its invaded area. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 133 publications
1
23
0
Order By: Relevance
“…The North American source of D. valens transported to China may have come from one or more locations, but most likely within the West group and possibly the PNW based on genetic studies (Cai et al, 2008; Cognato et al, 2005; Z. Liu et al, 2022; Taerum et al, 2016), while origination from Central or Northeast populations is suggested by symbiont community analyses (Q. Lu, Decock et al, 2009; M. Lu, Zhou, et al, 2009; Taerum et al, 2013, 2016). Further refinement of the North American source(s) invading China may be provided by population's primary attraction responses to β‐pinene or carene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The North American source of D. valens transported to China may have come from one or more locations, but most likely within the West group and possibly the PNW based on genetic studies (Cai et al, 2008; Cognato et al, 2005; Z. Liu et al, 2022; Taerum et al, 2016), while origination from Central or Northeast populations is suggested by symbiont community analyses (Q. Lu, Decock et al, 2009; M. Lu, Zhou, et al, 2009; Taerum et al, 2013, 2016). Further refinement of the North American source(s) invading China may be provided by population's primary attraction responses to β‐pinene or carene.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, populations we have tested in Washington, Oregon and northeastern California, where β‐pinene produces the strongest response, can be removed from the source pool. Genomic analyses show northeastern California and western Montana populations to more closely align with beetles in China than US populations from Arizona‐Colorado, or Wisconsin‐Minnesota (Z. Liu et al, 2022). The California collection site for Z. Liu et al (2022) is in a general area where some D. valens populations respond more strongly to carene than β‐pinene (Erbilgin et al, 2007), while no comparison tests for these two kairomones have been conducted in Montana.…”
Section: Discussionmentioning
confidence: 99%
“…The draft genome is obtained by first assembling long reads and then polishing the results with short reads, which has been widely used in genome assembly research for different organisms recently 14 18 . NextDenovo v2.5.0 ( https://github.com/Nextomics/NextDenovo ) was used to assemble the initial assembly with ONT sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, high-quality genomes of Dendroctonus spp. recently published provide valuable references for interaction studies between the Curculionoidea superfamily and their host terpenoids [47,48]. In this context, some rapidly expanded and positively selected genes related to metabolic capacity, including cytochrome P450 and glutathione S-transferase gene families, were thought to promote Dendroctonus adaptations to oleoresin terpenoids in conifers [48,49].…”
Section: A Global Picture Of Pagiophloeus Tsushimanus Transcriptomementioning
confidence: 99%
“…recently published provide valuable references for interaction studies between the Curculionoidea superfamily and their host terpenoids [47,48]. In this context, some rapidly expanded and positively selected genes related to metabolic capacity, including cytochrome P450 and glutathione S-transferase gene families, were thought to promote Dendroctonus adaptations to oleoresin terpenoids in conifers [48,49]. Consequently, in the future, genome sequence of P. tsushimanus deserves in-depth studies to perform a comparative analysis with genomes of Dendroctonus spp.…”
Section: A Global Picture Of Pagiophloeus Tsushimanus Transcriptomementioning
confidence: 99%